2004
DOI: 10.3310/hta8300
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the effectiveness and cost-effectiveness, and economic evaluation, of myocardial perfusion scintigraphy for the diagnosis and management of angina and myocardial infarction

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 3 publications
1
56
0
3
Order By: Relevance
“…A recent meta-analysis of MPI studies with angiographic end points found a median sensitivity of 81% and specificity of 65%. 37 When we applied a referral bias correction to these data (see Methods), 19 using recent estimates of angiography referral rates for positive (48.2%) and negative (6.2%) MPI results, 38 the unbiased estimates of MPI performance were 35% sensitivity and 94% specificity. These estimates are very similar to the core-laboratory results obtained in this study, which had minimal referral bias by design, and suggest that our results are consistent with the literature after verification bias removal.…”
Section: Limitationsmentioning
confidence: 99%
“…A recent meta-analysis of MPI studies with angiographic end points found a median sensitivity of 81% and specificity of 65%. 37 When we applied a referral bias correction to these data (see Methods), 19 using recent estimates of angiography referral rates for positive (48.2%) and negative (6.2%) MPI results, 38 the unbiased estimates of MPI performance were 35% sensitivity and 94% specificity. These estimates are very similar to the core-laboratory results obtained in this study, which had minimal referral bias by design, and suggest that our results are consistent with the literature after verification bias removal.…”
Section: Limitationsmentioning
confidence: 99%
“…Becauseofi ts wide availability, noninvasiveness, and high diagnostic performance, myocardial perfusion imaging (MPI) using SPECT has become of common practice for coronary artery disease (CAD) screening, characterization, and follow-up (1,2). The standard semiquantitative approach based on the analysis of reversible perfusion defects between stress and rest images has excellent sensitivity and negative predictive value for ischemic lesion detection (3).…”
mentioning
confidence: 99%
“…21 The diagnostic performance of SPECT in this substudy and in the main CE-MARC trial is lower than in previous studies (sensitivity range, 63%-93%; specificity range, 10%-90%), although the data lie within the published 95% confidence interval. 25,26 The reason is that CE-MARC was a prospective study, deliberately designed to minimize any selection (referral) bias. In contrast, the trials that contribute to the majority of prior SPECT data are all subject to either a pretest selection bias (only patients warranting coronary angiography enrolled) or a posttest selection bias (only positive SPECT cases referred for coronary angiography), leading to overestimation of the true diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%